Memórias em crônicas: itinerários da cidade João Pessoa na produção de Gonzaga Rodrigues - Córdula, Ana Cláudia Cruz (2019)
Memory is the basis for the construction of life, of the consciousness of an individual and, therefore, of social groups, starting by the formation of the own society. It is by means of it that occurs the most varied records in the processes of identification of subjects with the space in which they are inserted in, as well as the consequent relations that are established from this identification. The present research is aimed to reflect about the information extracted from a set of chronicles, comprehending them as a document capable of emerging the memory of the cities. In this context, it is analyzed a corpus composed by chronicles produced by Gonzaga Rodrigues, which are about the city of João Pessoa, Paraíba. By making known the intrinsic memories in the chronicles, as intellectual production of Gonzaga Rodrigues, a writer from Paraíba, more deeply, it is considered the social action of discourse falling on society. The main objective is to analyze the intellectual production of Gonzaga Rodrigues, specifically the chronicle as a memorialistic document and source of information capable of resignifying the memory of the city of João Pessoa, helping in the construction and in the strengthening of local identities. It is understood that the chronicles produced by the columnist has originally the function of being an information support, but he ends up assuming this attribution according to the situation and use. Beyond the debate between city and chronicle, it is interesting to retain here, in a particular way, is the fact of the chronicle can be considered an information artifact. The selected theoretical foundation is sustained the supposition that the representations elaborated by the columnist of Paraíba about himself and his actions are contained in his daily practices. The analyzed corpus was composed by nine chronicles, produced and published by Gonzaga Rodrigues in two literary works: "Filipéia e outras saudades" e "Café Alvear: ponto de encontro perdido". The adopted methodological approach is exploratory and descriptive and delineated by a documentary study. It is used in the methodology the model of indicial analysis based on the formulation of the indicial paradigm, assuring to explicit, in a more complete way, the relation with the study object. They are presented some inferences about the chronicle and its mode of functioning, sustaining the conviction that chronicle is literary art, although it is inserted in a precarious and unstable territory, and the columnist is that one capable of constructing an existence beyond the daily life, revealing himself as a source of information and memory. Articulating theoretical reflections about the relations between memory and identity, especially the consideration of identity as historic evidence, the discussion is about the constitution of a social memory in order to identify and legitimate the information of chronicle that, in its memorialistic bias, carries information capable of strengthening the identity aspects of the city: its streets, people, places. Insofar as the columnist publishes memories about the city, he enhances the identity aspects, once memory is the fundamental element for the identity construction.